Design, synthesis, structural characterization, cytotoxicity and computational studies of Usnic acid derivative as potential anti-breast cancer agent against MCF7 and T47D cell lines - Roney, Miah; Wong, Kelvin Khai Voon; Uddin, Md. Nazim; Rullah, Kamal; Septama, Abdi Wira; Antika, Lucia Dwi; Mohd Fadhlizil Fasihi, Mohd Aluwi (Elsevier Ltd, 2025)
Development of novel inhibitors is necessary to counteract the rising prevalence of breast cancer (BC) in women in recent years, as evidenced by the side-effect profiles of a few clinically approved inhibitors. In this study, the usnic acid derivative (UA1) was synthesized due to the effectiveness of usnic acid (UA) against BC cell line. Furthermore, the structure of synthesized compound was determined using FT-IR, 1H NMR, 13C NMR, HSQC, and HMBC spectroscopic techniques. The anticancer potential of UA1 was assessed using the MTT assay on two different cell lines of BC including MCF7 and T47D. To ascertain the binding affinity and stability of the docking complex, further procedures included the in silico molecular docking, molecular dynamic simulation, principal component analysis, and binding free energy experiments. The cytotoxicity results show that the UA1 exhibits strong antitumor activities and comparable effects against BC cell lines with the IC50 values of 9.21 µM for MCF7 cell and 14.8 µM for T47D cell, respectively, where the positive control cisplatin showed the IC50 values of 8.95 µM for MCF7 cell and 10.9 µM for T47D cell. Additionally, the molecular docking results of UA1 showed that it interacts strongly into the active site of target protein. Molecular dynamics simulation results also revealed that the docking complex was formed stability with the RMSD and RMSF values of 0.50 nm and 0.19 nm, respectively. According to the PCA analysis, the target protein displays good conformational space behaviour when bound with UA1. Furthermore, the UA1 showed the free binding energy value of −18.52 kcal/mol with the target protein, which indicating that UA1 may prevent BC.